Insights into the Mechanisms of Lactobacillus acidophilus Activity against Entamoeba histolytica by Using Thiol Redox Proteomics - Lotem Sarid; Eva Zanditenas; Jun Ye; Meirav Trebicz-Geffen; Serge Ankri (MDPI AG, 2022)
Amebiasis is an intestinal disease transmitted by the protist parasite, Entamoeba histolytica. Lactobacillus acidophilus is a common inhabitant of healthy human gut and a probiotic that has antimicrobial properties against a number of pathogenic bacteria, fungi, and parasites. The aim of this study was to investigate the amebicide activity of L. acidophilus and its mechanisms. For this purpose, E. histolytica and L. acidophilus were co-incubated and the parasite's viability was determined by eosin dye exclusion. The level of ozidized proteins (OXs) in the parasite was determined by resin-assisted capture RAC (OX-RAC). Incubation with L. acidophilus for two hours reduced the viability of E. histolytica trophozoites by 50%. As a result of the interaction with catalase, an enzyme that degrades hydrogen peroxide (H2O2) to water and oxygen, this amebicide activity is lost, indicating that it is mediated by H2O2 produced by L. acidophilus. Redox proteomics shows that L. acidophilus triggers the oxidation of many essential amebic enzymes such as pyruvate: ferredoxin oxidoreductase, the lectin Gal/GalNAc, and cysteine proteases (CPs). Further, trophozoites of E. histolytica incubated with L. acidophilus show reduced binding to mammalian cells. These results support L. acidophilus as a prophylactic candidate against amebiasis.